SIMULASI MANAJEMEN IRIGASI HEMAT AIR UNTUK BUDIDAYA PADI METODE SRI (SYSTEM OF RICE INTENSIFICATION) DI ARAS DAERAH IRIGASI - , SUPARMI, Prof. Dr. Ir. Sigit Supadmo Arif, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Current and future great challenge of agriculture sector is to provide sufficient food for rapidly increasing number of people with less water availability. One opportunity to solve the situation is to formulate a method of water saving in rice cultivation. SRI (System of Rice Intensification) is a method to increase the productivity of irrigated rice cultivation by changing the irrigation management. Based on the fact is needed a research. The research was conducted at sandy loam field of Mejing irrigated command area, Bantul District, Yogyakarta Special Province. The detail studyâs aims were (i) to compute and calculate optimum transpiration for SRI cultivation method based on crop yield â water use simulation model, (ii) to determine effect of different water saving application for SRI yield, and (iii) to simulate irrigation management at irrigated command area to plan appropriate irrigation management of SRI. To meet the goals were arranged field research treatments of SRI. The treatments were West Java farmerâs of SRI, controlled SRI and local specific farmerâs of SRI. The simulation result explained optimum water requirements at sandy loam field were at value of 1.990, 1.628 and 1.467 mm/planting season for West Java farmerâs of SRI, controlled SRI and local specific farmerâs of SRI respectively. The controlled SRI and local specific farmerâs of SRI saved more water than conventional rice farming system. Water saving was done by the intermittent irrigation so reduce that evaporation. Water saving was done by intermittent irrigation to reduce evaporation. Variation of water application did not affect SRI yield directly. The yield directly depends on seasonal yield factor (FTPM), vegetation yield factor (FTVT) and C Constanta. Optimum FTVT (value = 1) met when total actual transpiration at the vegetative and generative phase was at value 245,8 mm to 248,6 mm. Whereas optimum FTPM (value = 1) obtained when actual transpiration â¥ 433,8 mm. Simulation result demonstrated that the planting season II on the sandy loam field in Mejing irrigated command area with soil water table 1,4 m â 2,6 m, Mejing Weir was only able to supply 69,73% of total irrigated command area for SRI method cultivation.